Loss of Cln5 leads to altered Gad1 expression and deficits in interneuron development in mice. (17th July 2019) - Singh, Yajuvinder; Leinonen, Henri; Fazaludeen, Feroze; Jaronen, Merja; Guest, Debbie; Buckley, Noel; Byts, Nadiya; Oksa, Petra; Jalkanen, Kari; Iqbal, Imran; Huuskonen, Mikko; Savchenko, Ekaterina; et al.
Abstract: The Finnish-variant late infantile neuronal ceroid lipofuscinosis, also known as CLN5 disease, is caused by mutations in the CLN5 gene. Cln5 is strongly expressed in the developing brain and expression continues into adulthood. CLN5, a protein of unknown function, is implicated in neurodevelopment but detailed investigation is lacking. Using Cln5 −/− embryos of various ages and cells harvested from Cln5 −/− brains we investigated the hitherto unknown role of Cln5 in the developing brain. Loss of Cln5 results in neuronal differentiation deficits and delays in interneuron development during in utero period. Specifically, the radial thickness of dorsal telencephalon was significantly decreased in Cln5 −/− mouse embryos at embryonic day 14.5 (E14.5), and expression of Tuj1, an important neuronal marker during development, was down-regulated. An interneuron marker calbindin and a mitosis marker p-H3 showed down-regulation in ganglionic eminences. Neurite outgrowth was compromised in primary cortical neuronal cultures derived from E16 Cln5 −/− embryos compared with WT embryos. We show that the developmental deficits of interneurons may be linked to increased levels of the repressor element 1-silencing transcription factor, which we report to bind to glutamate decarboxylase ( Gad 1 ), which encodes GAD67, a rate-limiting enzyme in the production of gamma-aminobutyric acid (GABA). Indeed, adult Cln5 −/− mice presented deficits in hippocampal parvalbumin-positive interneurons. Furthermore, adult Cln5 −/− mice presented deficits in hippocampal parvalbumin-positive interneurons and showed age-independent cortical hyper excitability as measured by electroencephalogram and auditory-evoked potentials. This study highlights the importance of Cln5 in neurodevelopment and suggests that in contrast to earlier reports, CLN5 disease is likely to develop during embryonic stages.